Collaborative Supervision Strategy To Prevent Child Violence In Temporary Care Institutions - Nurhayati, Eti Sri (Jurnal Indonesia Sosial Sains, 2025)
Child abuse remains a serious issue in Child Care Centers, which serve as temporary care institutions for children of working parents—particularly mothers who are the main breadwinners. Several recent cases, including the death of an infant at Princess Childcare Bali, physical abuse in a Serpong daycare, and neglect at facilities such as Early Step in Pekan and Wensen School Indonesia in Depok, highlight the vulnerability of children in these settings. These incidents negatively affect children's growth and development and indicate systemic weaknesses in supervision and regulation. Data reveal that 44% of daycare centers operate without legal permits, 96% provide care services, yet only 33.3% of caregivers are certified. This reflects inadequate enforcement of care standards and fragmented oversight due to unclear inter-sectoral roles and responsibilities. This study uses a qualitative approach with a Systematic Literature Review (SLR) methodology to explore the current gaps in policy and institutional practice. The objective is to develop actionable policy recommendations that strengthen child protection in temporary care institutions. The findings point to a critical need for integrated, cross-sectoral supervision mechanisms and standardized caregiver certification requirements. The main policy recommendation is to revise and enhance the Child-Friendly District/City Evaluation Indicators to include clearer guidelines on childcare service regulation, oversight coordination, and caregiver competency standards. These measures are essential to improving institutional accountability and ensuring child safety and well-being in childcare facilities.